2015
DOI: 10.1186/s12876-015-0331-1
|View full text |Cite
|
Sign up to set email alerts
|

“A randomized, double-blind study of the effects of omega-3 fatty acids (Omegaven™) on outcome after major liver resection”

Abstract: BackgroundThe body is dependent on the exogenous supply of omega-3 polyunsaturated fatty acids (n3-PUFA). These essential fatty acids are key players in regulating metabolic signaling but also exert anti-inflammatory and anti-carcinogenic properties. The liver is a major metabolic organ involved in fatty acid metabolism. Under experimental conditions, n3-PUFA exert beneficial effect on hepatic steatosis, regeneration and inflammatory insults such as ischemic injury after surgery. Some of these effects have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The proportion and type of fats included in the diet influence the degree of inflammation and the risk of NCD. In this context, the intake of polyunsaturated fatty acids (PUFA), particularly the long-chain ones from the w-3 series (n-3 PUFA), is related to the reduction of the risk of cardiovascular diseases and death due to its anti-inflammatory potential [ 51 54 ]. Diets high in monounsaturated fatty acids (MUFA) have also been highlighted for their potential in reducing inflammation due to the lower expression of genes related to the synthesis of IL-6 [ 10 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion and type of fats included in the diet influence the degree of inflammation and the risk of NCD. In this context, the intake of polyunsaturated fatty acids (PUFA), particularly the long-chain ones from the w-3 series (n-3 PUFA), is related to the reduction of the risk of cardiovascular diseases and death due to its anti-inflammatory potential [ 51 54 ]. Diets high in monounsaturated fatty acids (MUFA) have also been highlighted for their potential in reducing inflammation due to the lower expression of genes related to the synthesis of IL-6 [ 10 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study should also inform on the V3FA activities in I/R, regeneration, and steatosis in patients. 46 The use of V3FA as a measure to expand the application of surgery to fatty liver, or lean liver requiring extended resection, comes with several advantages; the pre-operative administration of V3FA is simple, either as a food supplement or via intravenous injection (Omegaven). Therefore, little issues with compliance are expected, unlike for the currently recommended NAFLD treatment, that is, exercise combined with caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
“…68 These trials showed a greater ability to detect differences between treatment effects than classic endpoints such as 'any complication' or 'major complication' defined according to the Clavien-Dindo classification. The index has been used in large multi-centric studies, [69][70][71][72][73][74][75][76][77] notably as a benchmark endpoint for major surgery. 70 Exploring the potential added value of the comprehensive comprehensive index to standard assessment of postoperative morbidity, and to clarify potential controversies for its application, Clavien et al 78 reported that it yielded substantial additional value to the Clavien-Dindo classification in patients with more than one complication.…”
Section: Descriptionmentioning
confidence: 99%